Pulsed dose rate brachytherapy as the boost in combination with external beam irradiation in base of tongue cancer. Long-term results from a uniform clinical series - Bengt Johansson; Leif Karlsson; Johan Reizenstein; Mathias von Beckerath; Lennart Hardell; Jan Persliden (Journal of Contemporary Brachytherapy, 2011)
Purpose: To evaluate long time outcome with regard to local tumour control, side effects and quality of life of combined pulsed dose rate (PDR) boost and hyperfractionated accelerated external beam radiotherapy (EBRT) for primary base of tongue (BOT) cancers. Material and methods: Between 1994 and 2007, the number of 83 patients were treated with primary T1-T4 BOT cancers. Seven patients (8%) were T1-2N0 (AJCC stage I-II) and 76 (92%) patients were T1-2N+ or T3-4N0-2 (AJCC stage III-IV). The mean estimated primary tumour volume was 15.4 (1-75) cm3. EBRT was given with 1.7 Gy bid to 40.8 Gy to primary tumour and bilateral neck lymph nodes in 2.5 weeks. PDR boost of 35 Gy and a neck dissection in clinical node positive case was performed 2-3 weeks later. The patients were followed for a median of 54 (2-168) months. Results: The 2-, 5- and 10-years rates of actuarial local control were 91%, 89% and 85%, overall survival 85%, 65% and 44%, disease free survival 86%, 80% and 76%, respectively. The regional control rate was 95%. Six patients (7%) developed distant metastases. A dosimetric analysis showed a mean of 100% isodose volume of 58.2 (16.7-134) cm3. In a review of late complications 11 cases of minor (13%) and 5 of major soft tissue necroses (6%), as well as 6 cases of osteoradionecroses (7%) were found. The patients median subjective SOMA/LENT scoring at last follow up was as follow: grade 0 for pain and trismus, grade 1 for dysphagia and taste alteration, and grade 2 for xerostomia. Global visual- analogue-scale (VAS) scoring of quality of life was 8. Conclusion: Local and regional tumour control rate was excellent in this treatment protocol. The data shows the PDR boost as at least as effective as published continuous low dose rate (CLDR) results.